2014
DOI: 10.2147/ijn.s57929
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of silica nanoparticle toxicity after topical exposure for 90 days

Abstract: Silica is a very common material that can be found in both crystalline and amorphous forms. Well-known toxicities of the lung can occur after exposure to the crystalline form of silica. However, the toxicities of the amorphous form of silica have not been thoroughly studied. The majority of in vivo studies of amorphous silica nanoparticles (NPs) were performed using an inhalation exposure method. Since silica NPs can be commonly administered through the skin, a study of dermal silica toxicity was necessary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…For example, Ryu et al . 17 reported that SiNPs had no toxic effects, including no such effects on internal organs, after dermal topical application of SiNPs for 90 days. In another report, SiNPs elicited only minimal biological toxicity in intestinal cells compared to marked toxicity caused by zinc oxide NPs 18 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ryu et al . 17 reported that SiNPs had no toxic effects, including no such effects on internal organs, after dermal topical application of SiNPs for 90 days. In another report, SiNPs elicited only minimal biological toxicity in intestinal cells compared to marked toxicity caused by zinc oxide NPs 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have focused on their unique physical and chemical characteristics as well as the potential adverse effects arising from these properties. Among the many kinds of these nanomaterials, silica (SiO 2 ) nanoparticles (NPs) have great promise for applications in biosensors, DNA delivery, sunscreen lotions, and cancer therapy 1 2 . Despite many efforts to understand the potential hazardous effects of silica NPs, including oxidative stress and pro-inflammatory responses in rodents and RAW264.7 cells 3 , autophagy and endothelial dysfunction via the PI3K/Akt/mTOR signaling pathway 4 , acute inflammation and hepatocyte necrosis through neutrophil-mediated liver injury 5 , as well as apoptosis and changes of the cell cycle in HaCaT cells 6 , there is still a lack of clear understanding of the cytotoxic effects of silica NPs on components of the immune system that provide the first line of defense, such as neutrophils, monocytes, and macrophages.…”
mentioning
confidence: 99%
“…The crystalline form of silica is toxic to alveolar cells and can induce irreversible pulmonary silicosis 23 , 24 . Conversely, amorphous silica, such as nonporous silica particle, is considered relatively biologically safe because of its biodegradability 25 – 27 . Biodegradation and clearance are essential for biomedical use of nanoparticles because chronic accumulation of nanoparticles in human bodies can lead to serious long term complications.…”
Section: Discussionmentioning
confidence: 99%